Pendidikan Kemaritiman dan Sosialisasi Biota Laut Dilindungi Sebagai Upaya Keberlanjutan Sumberdaya Perikanan di Desa Galo-Galo - Nurafni, Nurafni; Koroy, Kismanto; Asy’ari, Asy’ari; Alwi, Djainudin; Wahab, Iswandi; Muhammad, Sandra Hi; Kodobo, Jihar; Pina, Fijai; Alican, Ismawati (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
Raising public awareness about the threats to protected marine life in Galo-Galo Village is crucial, given the continued decline in the population of these species. Through maritime outreach and education, it is hoped that the community will understand the importance of marine resource sustainability. This activity not only provides information about protected species but also encourages the community to protect and monitor marine life and teaches environmentally friendly fishing techniques. This outreach and education program is scheduled to take place from November 13 to 16, 2025, at various locations, including elementary schools, Islamic junior high schools, village halls, and frequently visited coastal areas. This activity will involve 35 students from elementary schools and Islamic junior high schools, as well as 40 community members from the village. The implementation stages include surveys, observations, preparation, implementation, and closing. This activity is expected to provide students with a better understanding of protected animals and strengthen maritime education materials. With a comprehensive introduction to ecosystems, marine resources, coastal management, and maritime culture, students are expected to be more aware of the importance of sustainability. Community outreach also yielded positive results, with interactive dialogues increasing participation and awareness of marine biota protection issues.ABSTRAKPeningkatan kesadaran masyarakat tentang ancaman terhadap biota laut yang dilindungi di Desa Galo-Galo menjadi sangat penting, mengingat populasi spesies tersebut terus menurun. Melalui sosialisasi dan edukasi kemaritiman, diharapkan masyarakat dapat memahami pentingnya keberlanjutan sumber daya laut. Kegiatan ini tidak hanya memberikan informasi mengenai spesies yang dilindungi, tetapi juga mendorong masyarakat untuk menjaga dan mengawasi biota laut serta mengajarkan teknik penangkapan ikan yang ramah lingkungan. Program sosialisasi dan edukasi ini direncanakan berlangsung dari tanggal 13 hingga 16 November 2025, di lokasi-lokasi seperti Sekolah Dasar, Madrasah Tsanawiyah, balai desa, dan area pantai yang sering dikunjungi. Kegiatan ini melibatkan 35 siswa dari sekolah dasar dan madrasah, serta 40 anggota masyarakat desa. Tahapan pelaksanaan mencakup survei, observasi, persiapan, pelaksanaan, dan penutupan. Dari kegiatan ini, diharapkan siswa mendapatkan pemahaman yang lebih baik mengenai hewan yang dilindungi serta memperkuat materi pendidikan kemaritiman. Dengan pengenalan menyeluruh tentang ekosistem, sumber daya laut, pengelolaan pantai, dan budaya maritim, siswa diharapkan lebih menyadari pentingnya kelestarian. Sosialisasi dengan masyarakat juga menunjukkan hasil positif, dengan dialog interaktif yang meningkatkan partisipasi dan kepedulian terhadap isu perlindungan biota laut.